Sliding Mode Control for Active Suspension System with Data Acquisition Delay - Alves, Uiliam Nelson L. T. [UNESP]; Garcia, Jose Paulo F. [UNESP]; Teixeira, Marcelo C. M. [UNESP]; Garcia, Saulo C. [UNESP]; Rodrigues, Fernando B. [UNESP] (Hindawi Publishing Corporation, 2014)
This paper addresses the problem of control of an active suspension system accomplished using a computer. Delay in the states due to the acquisition and transmission of data from sensors to the controller is taken into account. The proposed control strategy uses state predictors along with sliding mode control technique. Two approaches are made: a continuous-time and a discrete-time control. The proposed designs, continuous-time and discrete-time, are applied to the active suspension module simulator from Quanser. Results from computer simulations and experimental tests are analyzed to show the effectiveness of the proposed control strategy.